2019
DOI: 10.1007/978-3-030-14094-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Average Case - Worst Case Tradeoffs for Evacuating 2 Robots from the Disk in the Face-to-Face Model

Abstract: The problem of evacuating two robots from the disk in the face-to-face model was first introduced in [16], and extensively studied (along with many variations) ever since with respect to worst case analysis. We initiate the study of the same problem with respect to average case analysis, which is also equivalent to designing randomized algorithms for the problem. First we observe that algorithm B2 of [16] with worst case cost Wrs (B2) := 5.73906 has average case cost Avg (B2) := 5.1172. Then we verify that non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…While most evacuation type problems have focused on the worst-case scenarios, Chuangpishit et al [26] started to explore the algorithms' average case analysis for the problem of evacuating two robots from the disc in the face-to-face model. They found that while worst-case performance of an algorithm improves, the average-case performance worsens for all the previously studied algorithms.…”
Section: Evacuation Problems and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While most evacuation type problems have focused on the worst-case scenarios, Chuangpishit et al [26] started to explore the algorithms' average case analysis for the problem of evacuating two robots from the disc in the face-to-face model. They found that while worst-case performance of an algorithm improves, the average-case performance worsens for all the previously studied algorithms.…”
Section: Evacuation Problems and Literature Reviewmentioning
confidence: 99%
“…We previously discussed that our intention is to consider the average-case sce- It is also important to mention the results (Figure 3.7b) of a performance analysis [26] recently done for benchmark algorithms B 2 . Figure 3.7b shows a consolidated e ciency-plot for various algorithms as we consider various combinations of and for varying detour-point C as shown in Figure 3.…”
Section: Benchmark Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The communication model being used may be either wireless [10] or F2F [7,16,19]. Search and evacuation problems with a combinatorial flavour have been recently considered in [12,13] and search-and-fetch problems in [21,22], while [9] studied average-case/worst-case trade-offs for a specific evacuation problem on the disk. The interested reader may also wish to consult a recent survey paper [14] on selected search and evacuation topics.…”
Section: Related Workmentioning
confidence: 99%
“…A setting similar to ours is presented in the recent works [17,18,21,22,36,12,15] where algorithms are presented in the wireless and non-wireless (or face-to-face) communication models for the evacuation of a team of robots. The "search domain" in [17,18,21,15] is a unit circle (while in [22] the search domain is a triangle or square), however, unlike our search problem, in these papers all the robots are required to evacuate from an unknown exit on the perimeter. Moreover, in none of these papers is there a treasure to be fetched to the exit.…”
Section: Related Workmentioning
confidence: 99%